2003
DOI: 10.4067/s0034-98872003001100014
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia antimicrobiana en Helicobacter pylori: aspectos clínicos y moleculares

Abstract: Helicobacter pylori is a relevant pathogen for gastroduodenal diseases in human beings. Although its eradication often improves gastroduodenal diseases, H pylori is acquiring an elevated rate of resistance to various antimicrobials, such as metronidazole, clarithromycin, tetracycline and amoxicillin. Multi-drug resistance is a major problem to select the appropriate treatment of infectious diseases. To improve our understanding on the complexity of the problem, in this article we review the resistance mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
4
0
4
Order By: Relevance
“…This difference is attributed to impaired environmental hygienic conditions frequently observed in developing countries, thus determining frequent exposure to H. pylori (11, 12, 19, 21, 24). Previous studies in Chile, reported isolation frequencies ranging from 60 to 70% in adults (28). In this study, however, we found a lower isolation frequency (41.3%).…”
Section: Discussionmentioning
confidence: 95%
“…This difference is attributed to impaired environmental hygienic conditions frequently observed in developing countries, thus determining frequent exposure to H. pylori (11, 12, 19, 21, 24). Previous studies in Chile, reported isolation frequencies ranging from 60 to 70% in adults (28). In this study, however, we found a lower isolation frequency (41.3%).…”
Section: Discussionmentioning
confidence: 95%
“…Las evidencias indican que la resistencia a antibióti-cos en H pylori son esencialmente debidas a mutaciones cromosomales 10,[17][18][19]23 . Una consecuencia importante de este hecho es que la transmisión de la resistencia ocurre fundamentalmente desde un microorganismo a otro en forma vertical, en que las mutaciones aparecen en la descendencia y, por lo tanto, se observa un progresivo incremento en la resistencia debido a la presión impuesta por el uso de los antibióticos.…”
Section: Discussionunclassified
“…Para alcanzar el éxito en la erradicación de la bacteria ha sido necesario combinar al menos dos antibióticos y una droga que disminuya la secreción gástrica, ya sea un inhibidor de la bomba de protones o un antagonista de los receptores H2. El metronidazol (Mtz) es uno de los antibióticos utilizados en el tratamiento de la erradicación de H pylori 10 . Tasas altas de resistencia a Mtz se han observado en aislados clínicos a nivel mundial, 90% en India, 50% o más en Estados Unidos y Europa Occidental y 40,6% en Corea 10-12 , la cual puede variar en grupos de pacientes de acuerdo a la edad, sexo, enfermedades y lugares de residencia, lo que afecta negativamente en la eficiencia del tratamiento 10,13,14 .…”
Section: Background: Helicobacter Pylori Is a Pathogenic Bacterium Thunclassified
See 2 more Smart Citations